The Influence of Human Capital, Relational Capital, Organizational Capital, and the Information Technology Utilization on the ASN Performance in the Regional Social Services of the North Sulawesi Province Government - Mangli, Lili; Dotulong, Lucky O.H.; Lumintang, Genita G. (International Journal of Information Technology and Education, 2023)
The Social Service is the technical implementing element of Regional Government in the social sector which is tasked with carrying out regional autonomy authority in the field of social welfare services so that good performance is very much needed. Data collection in this research involved all ASNs at the Regional Social Service of North Sulawesi Province as respondents, namely 144 people. This research aims to analyze the influence of Human Capital, Relational Capital, Organizational Capital, and the Use of Information Technology on the performance of ASN of the Regional Social Service of North Sulawesi Province. The results of this research are (1) Human Capital has a positive and significant effect on ASN Performance at the North Sulawesi Province Regional Social Service (2) Relational Capital has a positive and significant effect on ASN Performance at the North Sulawesi Province Regional Social Service (3) Organizational Capital has a positive and significant effect significant impact on the performance of ASN in the Regional Social Service of North Sulawesi Province (4) Utilization of IT has a positive and significant effect on ASN Performance in the Regional Social Service of North Sulawesi Province (5) Human Capital, Relational Capital, Organizational Capital, and Utilization of IT together have an influence significant impact on the performance of ASN at the Regional Social Service of North Sulawesi Province.